FRACTIONATION AND EVALUATION OF ANTIDIABETIC, ANTIHYPERLIPIDEMIC AND ANTIOXIDANT ACTIVITY OF DECALEPIS HAMILTONII and SHOREA TUMBUGGAIA - V, RAGINI (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The aim of study was to evaluate antidiabetic, hypolipidemic and antioxidant activities of the fractions of the roots of Decalepis hamiltonii and leaves of Shorea tumbuggaia in experimentally induced diabetic rats. Alloxan (150mg/kg), intraperitoneal) was used to induce hyperglycemia. Administration of different fractions at different doses once daily up to 28days to diabetic rats reduced blood glucose and glycosylated hemoglobin, and increased insulin levels significantly. Triglycerides (TG), total cholesterol (TC), VLDL and LDL levels were significantly decreased, whereas, HDL levels were increased. The fractions also significantly reduced reactive thiobarbituric acid levels (TBARS), super oxide dismutase (SOD) and increased the levels of reduced glutathione (GSH) and catalase (CAT) when compared to the diabetic-control animals. D. hamiltonii and S.tumbuggaia was assessed for in-vitro antioxidant activity by DPPH (2, 2-diphenyl-1-picrylhydrazyl), hydrogen peroxide and reducing power model. Significant in-vitro antioxidant activity was observed in all the models. From the results, it is evident that alcoholic fractions of the roots of D.hamiltonii can be effectively used as antidiabetic, hypolipidemic and antioxidant activity. Â  Key words: antidiabetic, antioxidant, hypolipidemic, fractions, Decalepis hamiltonii